АРҚА-БАТЫС ҚЫЗЫЛҚУМЫНДА ТҮСКИ ҚУМ ТЫШҚАНЫНЫҢ (MERIONES MERIDIANUS PALL) КӨБЕЙИЎИ, ЖАС, ЖЫНЫС СТРУКТУРАСЫ - Дж.Алламуратов, Б.; Асенов, Г.А.; Есимбетов, Р.М.; Сейтмуратов, Р.Қ. (SCIENCE and SOCIETY, 2021)
The article presents the results of the North-Western Kyzyl Kum inhabiting midday gerbils of reproduction of perennial average indicators, on the number of average indicators of emryos. It is substantiated that it is related to the drying up of the Aral Sea and changes in ecological indicators, adaptations and conservation of the number of populations.
Keywords: dynamics of changes; population; embryo; reproduction; adaptation